IMPLEMENTATION TELEGRAM CHAT BOT ON STUDENT ORIENTATION PERIOD REGISTRATION SYSTEM FOR EFFICIENCY OF DATA MANAGEMENT - Faris Zaky Alfaiz; Maryam Maryam (Informatika, Universitas Jenderal Soedirman, 2021)
Orientation is a routine activity carried out by both public and private tertiary institutions. Universitas Muhammadiyah Surakarta (UMS) which is a private higher education institution also has several types of orientation, one of which is thePeriod of Ta'aruf the Muhammadiyah Student Association (MASTA IMM). IMM. IMM MASTA implementation that has occurred so far in the data processing process is still done manually, so there is often the same data and the time to manage the data is less effective and efficient. This study aims to design a MASTA IMM registration system using Telegram bot to simplify and streamline time in data management and class division. The method used in this research is themethod Waterfall modified, where the repair process is carried out only after the testing and evaluation stages. The development of this system will use the Telegram Bot API and theprogramming Pythonlanguage by utilizing library the provided. This system has several functions, including registration, adding and deleting data, dividing classes, and printing data intodocuments excel. This system has also been tested with good results. The test method used is the blackbox to find out the functionality of the system running properly. As well as testing the System Usability Scale (SUS) to evaluate the usefulness of the system with a final average result of 76.33, which means that the user agrees with the system that has been designed. This system is able to provide convenience during student registration and make it easier for admin in data management.